2006
DOI: 10.1136/oem.2004.019281
|View full text |Cite
|
Sign up to set email alerts
|

Validation of short term recall of mobile phone use for the Interphone study

Abstract: Volunteer subjects recalled their recent phone use with moderate systematic error and substantial random error. This large random error can be expected to reduce the power of the Interphone study to detect an increase in risk of brain, acoustic nerve, and parotid gland tumours with increasing mobile phone use, if one exists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
140
4
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(159 citation statements)
references
References 19 publications
13
140
4
2
Order By: Relevance
“…The timing of data collection between interviews and questionnaires are far enough apart that Divan et al mothers with delayed development children were unlikely systematically to under-or overestimate using a cell phone during pregnancy compared to mothers of children with no delayed development. In general, research looking at the agreement between self-reported cell phone use and usage measured by billing or subscription records concludes that individuals tend to overestimate call duration and underestimate the number of calls (29,30). As participation in each round of interviews and questionnaires was voluntary for mothers, it is possible that data were collected for mothers and children participating in the DNBC at only some time points such as 6 months and age 7 years and not have information available at 18 months for the infant.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of data collection between interviews and questionnaires are far enough apart that Divan et al mothers with delayed development children were unlikely systematically to under-or overestimate using a cell phone during pregnancy compared to mothers of children with no delayed development. In general, research looking at the agreement between self-reported cell phone use and usage measured by billing or subscription records concludes that individuals tend to overestimate call duration and underestimate the number of calls (29,30). As participation in each round of interviews and questionnaires was voluntary for mothers, it is possible that data were collected for mothers and children participating in the DNBC at only some time points such as 6 months and age 7 years and not have information available at 18 months for the infant.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of past mobile phone use are subject to random error, as recall even in the short term has been shown to be inaccurate. [26][27][28][29] Over-reporting of the amount of mobile phone use by 50-100% has been common. This is likely to attenuate any true relationship between exposure and outcome, and it might distort dose-response.…”
Section: Discussionmentioning
confidence: 99%
“…Information about the distribution of the multiplicative error factor e was available from INTERPHONE validation studies in which short-term recall of volunteer subjects was compared with actual usage patterns recorded by mobile phone service providers or software-modified mobile phones (Vrijheid et al, 2006). The ratio of recalled to actual phone use followed a log-normal distribution.…”
Section: Recall Biasmentioning
confidence: 99%
“…Recall errors may arise from errors in an individual's reported history of use of mobile telephones, in particular from errors in the cumulative amount of phone use reported (Vrijheid et al, 2006). If such errors occur randomly, they usually bias risk estimates for dichotomous and continuous exposures and trend effects for ordered polytomous exposures towards the null (no effect).…”
Section: Introductionmentioning
confidence: 99%